STUDY OF OPTIMUM CONDITION FOR ALKALINE PROTEASEPRODUCTION FROM LOCAL ISOLATE OF Aspergillus niger - Abdul Sahib, Riyad (Iraqi Journal of Science, 2024)
Extracellular alkaline protease production by Aspergillus niger was studied withthe presence of different carbon and nitrogen sources availability in batch culturecondition .A. niger showed better protease production in the presence of organicnitrogen sources compare to inorganic nitrogen sources in the medium, whichconsist of 1% glucose as carbon source, 1.5% casein hydrolysate as nitrogen sourceand 1% Nacl at initial pH=10 on rotary shaker incubator 140 rpm at 40 ºC for 5days.